Implementation of circles of quality of attention in services of health and satisfaction of the external user of Carlos Showing Ferrari Hospital and Hermilio Valdizán Medrano Hospital, Huánuco 2007 - 2008 - Fonseca Livias, Abner A. (2009)
This study was carried out with the aim to determine the importance of the implementation of the quality circles of medical care in the satisfaction of the external user in the Hermilio Valdizan Regional Hospital and Carlos Showing Ferrari center health, in the province and department of Huánuco. The study was cuasiexperimental, prospective, longitudinal and with chronological series designs. The sample was 374 external patients, distributed in an equitably way, evaluated earlier and after the experiment with a satisfaction questionnaire. In a previous evaluation was classified the critical services of health (external doctor´s offices, emergency and programs) where the dissatisfaction in the time of waiting to receive medical care was a 67,1 %, the inadequate communication 69,5 % and the maltreatment by the personnel of health 67,4 %. The latter results of the experimental group show suitable communication 43,0%, with well-treated 46,3%; their hypotheses were contrasted with Mann- Whitney Test, 95% level of significance the W is 45815 and 46 376 respectively, indicating that it is significant with 0.0000, accepting the Hi in both cases. In the time of waiting, the dissatisfaction still persists in both groups in average 59%; the hypotheses were contrasted with the T student,95% with level of reliability, 0.05 y 344 degrees of release, obtaining the T-140 value and P 0,082, that indicates the acceptance of the null hypothesis. In conclusion the implementation of quality circles has improved the satisfaction in the community and the treatment to external patient; but not about the time of waiting.